Use of Birth Certificates to Examine Maternal Occupational Exposures and Autism Spectrum Disorders in Offspring. Issue 1 (29th January 2013) - Windham, Gayle C.; Sumner, Austin; Li, Sherian X.; Anderson, Meredith; Katz, Elizabeth; Croen, Lisa A.; Grether, Judith K.
<x xml:space="preserve">Abstract</x> The continuing rise in the prevalence of autism spectrum disorders has led to heightened interest in the role of nongenetic factors, including exogenous exposures, but little research has been conducted. To explore a possible role in autism etiology, we used data available from our prior studies to examine potential occupational exposures, as these may occur at higher levels than environmental exposures. Parental occupation was obtained from birth certificates for 284 children with autism and 659 controls, born in 1994 in the San Francisco Bay Area. Self‐reported occupation and industry were coded into eight exposure/chemical groups based on potential neurotoxicity or reprotoxicity by a board‐certified physician in occupational medicine and an industrial hygienist blinded to case‐control status. Mothers of autistic children were twice as likely to work in occupations considered exposed (14.4%) as mothers of controls (7.2%) (adjusted odds ratio [AOR] 2.3 [95% confidence interval CI 1.3–4.2]). The exposure categories of the greatest frequency among case mothers were exhaust and combustion products (AOR = 12.0 [95% CI 1.4–104.6]) and disinfectants (AOR = 4.0 [95% CI 1.4–12.0]). Paternal occupational exposure was not associated with autism, potentially consistent with a direct in‐utero exposure effect. There are several limitations of this hypothesis‐generating study, including lack of detail on workplace and job duties, leading to possible misclassification and low proportion exposed. However, this misclassification would not be biased by case‐control status and is unlikely to explain the associations we did find, suggesting that further research on exogenous exposures may yield useful etiologic clues. Autism Res 2013, ●●: ●●–●●. © 2013 International Society for Autism Research, Wiley Periodicals, Inc.